Diffraction Studies on Displacive Transitions in Copper Based Shape Memory Alloys. - Adiguzel, Osman (Int Union Crystallography, 2012)
[Abstract Not Available]
Keywords: Shape memory effect; martensite; layered structures; atom sizes